PERSEPSI LESBIAN TENTANG KEHAMILAN DI KOTA KEDIRI TAHUN 2015 - Iftitah Nur Rosyidah; Lingga Kusuma Wardani (Universitas STRADA Indonesia, 2017)
Gender is very influential in the emergence otf the appeal, such as the attraction to the same sex. Currently, many phenomena that developed in the lesbian world. In the era of globalization, a lesbian relationship is growing rapidly and they have faith that they can become pregnant lesbian couple. Target of this research this study was to explore perceptions about pregnancy lesbians in kediri. The design used is descriptive qualitative study sample was taken from among lesbians in Kediri are willing to do interviews, with a sample size 4 informants. The collection of data with the tape recorder through in-depth interviews to 4informans. The results showed that of the four informans who conducted the interview obtained about lesbian perceptions about pregnancy, some informans found in understanding about pregnancy, informans argued that the informans with her lesbian partner will become pregnant and obtain the expected offspring and can live happily by with their families. Howover, one informant (informants 1) realize that pregnancy is impossible because this informant already understand pregnancy will notoccur along with her lesbian partner. Based on the research showed that the informant still thinks will get offspring with her lesbian partner. It is hoped that someday informant can change their mindset and realize that their current situation is wrong and can be a woman like in general, so that they can come closer to God Almighty.